Xuanfei Formula inhibited RSV infection by normalizing the SREBP2-mediated cholesterol synthesis process - Qin, Huan; Luo, Jin; Zhao, Nan; Lou, Wange; Chen, Peng; Wang, Huihao; Pan, Zishu; Xiong, Xiaoli (Frontiers in Microbiology, 2024)
Background & Aims: Respiratory syncytial virus (RSV) is the major cause of lower respiratory tract infections in children and the elderly, often progressing to pneumonia and severe sequelae. However, there are currently no feasible and cost-effective interventions with proven efficacy for children, making medications with anti-RSV activity urgently needed. Traditional Chinese medicine has shown promising therapeutic efficacy in alleviating viral infection symptoms. Therefore, we aimed to develop effective strategies for RSV treatment based on traditional Chinese medicine.The infection status was assessed in BALB/c mice with or without Xuanfei Formula (XFF) treatment over a one-week period using H&E staining, cytokine assays and RSV titer testing after RSV challenge. Remarkably, on the first day of XFF intervention, both the pro-inflammation cytokine levels in the serum and RSV-N gene copies in the lung of mice were plummeted，compared to the RSV-infected group. This implied that XFF might possess the immune-independent anti-RSV capability. To elucidate the underlying mechanism, we employed transcriptome analysis followed by k-means analysis. The reversal effects of XFF against RSV primarily focused on the processes of innate and adaptive immunity. Additionally, we found that XFF administration corrected the disordered fatty acid and cholesterol metabolism processes during RSV infection. Lipidomics profiling indicated consistent cholesterol abundance with transcriptional changes but not fatty acids. Cholesterol synthesis-related genes mRNA levels and cholesterol synthesis intermediates detection supported XFF's repression upon cholesterol biosynthesis. Aberrantly increased cholesterol production has been reported as necessary for RSV infection. To mimic that, we observed lovastatin treatment inhibited RSV replication and pro-inflammation cytokine expression in vitro. Transcription factor prediction of differentially expressed genes (DEGs) involved in cholesterol synthesis implicated SREBP2. Through network pharmacology, stigmasterol and β-sitosterol were identified as the effective active ingredients within the XFF, with the help of further molecular docking and mass spectrum detection. In vitro experiments demonstrated β-sitosterol and stigmasterol reinforced the bonding between SCAP and INSIGs to inhibit SREBP2 cleavage maturation and consequent RSV infection. Conclusion: XFF exhibits excellent anti-RSV efficacy by inhibiting SREBP2mediated cholesterol synthesis to reduce RSV replication and ameliorate inflammation in the lung of infected mice.